2010
DOI: 10.1021/ma101473r
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Behavior of Poly(l-lactide) Having Low l-Isomer Content of 94% after Compressed CO2 Treatment

Abstract: The effect of compressed CO 2 treatment on the thermal behavior of poly(L-lactide) (PLLA) with low L-isomer content of 94% was studied by using differential scanning calorimetry (DSC) and temperature modulated DSC. It was shown that the treated samples displayed rich thermal transition signals during DSC heating, which is differ from the PLLA having high L-isomer content, including enthalpy relaxation, endothermic annealing, melting-recrystallization process, and cold crystallization. The results suggested tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 60 publications
1
43
0
Order By: Relevance
“…It was reported that both the lowered equilibrium melting point and decreased crystallization rate could lead to the reduction of critical temperature for generating the PLLA a 0 -and a-form crystals [60]. A previous study has evidenced that a crystals rather than a 0 ones were induced in the PLLA with an optical purity of 88 % by compressed CO 2 at temperatures as low as 65°C [50]. In contrast, the molecular weight was found to hardly affect the temperature range for polymorphism of PLLA [14].…”
Section: Crystal Form Of Samples Crystallized At T C Smentioning
confidence: 99%
See 1 more Smart Citation
“…It was reported that both the lowered equilibrium melting point and decreased crystallization rate could lead to the reduction of critical temperature for generating the PLLA a 0 -and a-form crystals [60]. A previous study has evidenced that a crystals rather than a 0 ones were induced in the PLLA with an optical purity of 88 % by compressed CO 2 at temperatures as low as 65°C [50]. In contrast, the molecular weight was found to hardly affect the temperature range for polymorphism of PLLA [14].…”
Section: Crystal Form Of Samples Crystallized At T C Smentioning
confidence: 99%
“…It is well known that the optical purity (OP) of PLLA strongly affects its crystallization kinetics and melting behavior [50][51][52][53][54]. The crystallization rate, crystallinity, and melting point decrease with a reduction of optical purity [52,53], and PLLA loses crystallizability when the level of OP is smaller than 76 % [54].…”
Section: Introductionmentioning
confidence: 99%
“…Based on those considerations, there is a clear interest in studying the interactions between CO 2 and PLA, and the modifications that such molecule could induce in the PLA material, which is suitable as a substitute of PET. For now, most of the related literature is focused on the effects of supercritical CO 2 (or conditions near to it) on the PLA properties, such as foaming properties [16], thermal behavior [17][18][19], hydrophobic drug encapsulation [20,21] or swelling [22,23]. Nevertheless, there is not enough available information related to the effects of CO 2 at conditions lower than its supercritical point, which are often the conditions encountered in food packaging and food processing.…”
Section: Introductionmentioning
confidence: 99%
“…The effects of compressed CO 2 on the crystallization behavior of polymers have been extensively studied . Because of the plasticization effects of CO 2 , the glass transition temperature and melting temperature of polymers decrease, resulting in the shifting of the crystallization temperature to lower values.…”
Section: Introductionmentioning
confidence: 99%